2009
DOI: 10.1074/jbc.m901189200
|View full text |Cite
|
Sign up to set email alerts
|

Novel Glutaredoxin Activity of the Yeast Prion Protein Ure2 Reveals a Native-like Dimer within Fibrils

Abstract: Ure2 is the protein determinant of the Saccharomyces cerevisiae prion [URE3]. Ure2 has structural similarity to glutathione transferases, protects cells against heavy metal and oxidant toxicity in vivo, and shows glutathione-dependent peroxidase activity in vitro. Here we report that Ure2 (which has no cysteine residues) also shows thiol-disulfide oxidoreductase activity similar to that of glutaredoxin enzymes. This demonstrates that disulfide reductase activity can be independent of the classical glutaredoxin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 45 publications
0
31
0
Order By: Relevance
“…The authors thus suggest that mutations have allowed URE2p to diversify and acquire additional functions as a prion and a repressor of nitrogen catabolism. It has been recently shown that ScUREp also shows thiol-disulfide oxidoreductase activity similar to that of glutaredoxins even if it does not possess cysteine residue [50]. Concerning the investigated fungi of our study, only C. albicans and S. cerevisiae exhibit the N-terminal prion domain; however, many other fungal sequences with shorter URE2p and deprived of the prion domain cluster are present in this class (Fig.…”
Section: The Ure2p Classmentioning
confidence: 66%
“…The authors thus suggest that mutations have allowed URE2p to diversify and acquire additional functions as a prion and a repressor of nitrogen catabolism. It has been recently shown that ScUREp also shows thiol-disulfide oxidoreductase activity similar to that of glutaredoxins even if it does not possess cysteine residue [50]. Concerning the investigated fungi of our study, only C. albicans and S. cerevisiae exhibit the N-terminal prion domain; however, many other fungal sequences with shorter URE2p and deprived of the prion domain cluster are present in this class (Fig.…”
Section: The Ure2p Classmentioning
confidence: 66%
“…S7A). Fungal and bacterial Ure2p proteins were known to be active as dimers (Wadington et al, 2009;Zhang and Perrett, 2009). Fungal Ure2p proteins did not show detectable GST activity toward the standard substrate CDNB, but they had GSH-dependent peroxidase activity (Zhang et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, non-prion domains have been shown to retain their structure and activity even within the prion aggregate (Baxa et al 2002Bai et al 2004;Krzewska et al 2007;Zhang et al 2008;Zhang and Perrett 2009). More importantly, amyloid fibers of PrD fragments are infectious when transfected into non-prioncontaining cells (King and Diaz-Avalos 2004;Tanaka et al 2004;Brachmann et al 2005;Diaz-Avalos et al 2005;Patel and Liebman 2007;Du et al 2008Du et al , 2010Alberti et al 2009).…”
Section: Models Of Prion Structuresmentioning
confidence: 99%